Counselling high achieving and creatively gifted children (2011)
Psychologists and educators have expressed widely divergent views on the nature of high achievers and the characteristics of creative and gifted children. This study sheds light on the nature and concept of high achievers as well as the creative and gifted children. Effort has also been made in this study to enumerate the characteristics of the gifted and creative persons. Finally, in this study, the counselling strategies to be employed to ensure that these Intellectual Wizards achieve higher in different areas of life and become more creatively gifted have been stated.